2014
DOI: 10.1016/j.invent.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Participant retention in an automated online monthly depression rescreening program: Patterns and predictors

Abstract: Internet-based mental health resources often suffer from low engagement and retention. An increased understanding of engagement and attrition is needed to realize the potential of such resources. In this study, 45,142 individuals were screened for depression by an automated online screener, with 2,539 enrolling in a year-long monthly rescreening study; they received a single monthly reminder email to rescreen their mood. We found that, even with such a minimal cohort maintenance strategy, a third of the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…filling in the first questionnaires, does not change their commitment quickly, these participants are likely to discontinue early. Gill et al [6] also observed the importance of commitment in their online monthly depression rescreening program of similar length as our study and with short questionnaires every month. Our analyses showed that the need of receiving a reminder for the first questionnaire predicts attrition at later questionnaires (Gill et al did not send reminder emails, so we unfortunately cannot assess this observation in their study).…”
Section: Discussionsupporting
confidence: 82%
“…filling in the first questionnaires, does not change their commitment quickly, these participants are likely to discontinue early. Gill et al [6] also observed the importance of commitment in their online monthly depression rescreening program of similar length as our study and with short questionnaires every month. Our analyses showed that the need of receiving a reminder for the first questionnaire predicts attrition at later questionnaires (Gill et al did not send reminder emails, so we unfortunately cannot assess this observation in their study).…”
Section: Discussionsupporting
confidence: 82%
“…Greater adherence among older and employed participants has been observed previously. 11,29 The effect of quality of life suggests that poor health may be a barrier to research participation, whereas the effect of help-seeking intentions may reflect a propensity towards agreeableness being associated with both helpseeking intentions and survey completion. The version effect (depression v. social anxiety) may be an artefact of the recruitment method; although recruitment for both versions of the survey occurred simultaneously, there were times when recruitment for one version may have been dominant (due to Facebook algorithms and fluctuations in public interest).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced digital interventions have also incorporated attributes of Web 2.0 such as social networking, text messaging, and the use of video. However, Internet interventions typically have high attrition and have so far failed to produce population effects [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%